Study of Degradation Products at Different MEA Based Capture Pilot Plants. (January 2016) - Dux, D.; Schallert, B.
Abstract: In the past, several research programs were undertaken at European Carbon Capture (CC) pilot plants. The results of these individual MEA based campaigns are brought together in order to better understand the solvent degradation at CC pilot plants. The data correlation analysis shows that nickel catalyzes significantly the formation of some degradation products (e.g. HEPO) at low concentrations of 2 mg/l. The iron impact was less clear than determined for nickel. All pilot plants show HEGly and HEPO as the main degradation products, followed by HEF. Within the group of carboxylic acids, formate is the major degradation product.